Protecting our environment: The need for South African youth with a mission and black consciousness - Baron, Eugene (HTS teologiese studies, 2021)
Christianity has contributed to environmental degradation. In terms of their role, the church youth are ipso facto part of such a contribution. However, an eco-theological diagnostic analysis cannot interpret the role of youth, especially black youth, through the same lenses. From a Black theological perspective, black youth’s role should be interpreted and discussed in terms of what Fanon and Biko describe as ‘self-hatred’ and the need for black consciousness. It is such self-hatred that gives rise to environmental degradation that is not articulated within various eco-theologians’ strategies towards care for the environment in a neo-colonial context in South Africa. The article argues that such a deficiency in eco-theological literature needs some attention to address the future black youth’s contribution to a friendlier environment. The author therefore suggests a ‘missional consciousness’ for one of the strategies for black youth in the quest for the black youth’s participation in environmental care.Contribution: This article contributes to the broader discourses on ecotheology. It affirms the contributions on human beings’ role towards the environment, but further highlights the inequality among human beings in neo-colonial context and how ecotheology should approach the ecological crisis with consideration to such a context. Therefore, the contribution brings into dialogue the post-colonial discourse, specifically the discourse of black consciousness, in relation to a missional consciousness in resolving the ecological crisis through the participation of church youth. Ecotheology has not specifically considered the notions of ‘missional consciousness’ and ‘black consciousness’ in its discourse on protection of the environment. The author relates this discussion specifically to church youth.